Multicomponent Cascade Synthesis of 1,4-Dihydropyridine Derivatives from Pyridines, Methyl Propiolate, and Aromatic Acids - Huang, Panpan; Peng, Xiangjun; Huang, Qing; Liu, Liangxian (Synlett, 2017)
A metal-free highly efficient synthesis of a wide range of 4-propenyl 1,4-DHPs from pyridines, methyl propiolate, and aromatic acids is described. The reactions are conducted under convenient conditions and provide products with excellent regioselectivity in good to excellent yields, with broad substrate scope.
Keywords: 1,4-DHPs; pyridines; methyl propiolate; aromatic acids; multicomponent reactions